WESTERN PHILOSOPHY - Madalimov Timur; Nurymbetova Zumrad Ruslanovna (TADQIQOTLAR.UZ, 2024)
Abstract This article is about the history of Western philosophy from its development among the ancient Greeks of Classical antiquity to the present. The idea of ‘Western Philosophy’ is the product of a legitimation project for European colonialism, through to post-second world war Pan-European identity formation and white supremacist projects. Thus argues Ben Kies (1917-1979), a South African public intellectual, schoolteacher, trade unionist, and activist-theorist. In his 1953 address to the Teachers’ League of South Africa, The Contribution of the Non-European Peoples to World Civilization, Kies became one of the first people to argue explicitly that there is no such thing as ‘Western philosophy’. In this paper, I introduce Kies as a new figure in the historiography of philosophy with important insights, relevant today. I outline his three key arguments: that ‘Western Philosophy’ is the product of political mythmaking, that it is a recent, largely mid-twentieth century fabrication, and that there is an alternative to ‘Histories of Western Philosophy’, namely ‘mixed’ or entangled histories. I show that Kies’ claims are supported both by contemporary scholarship and bibliometric analysis. I thus argue that Kies is right to claim that the idea of a distinctive, hermetically sealed ‘Western Philosophy’ is a recent, political fabrication and should be abandoned. We should instead develop global, entangled historiography to make sense of philosophy and its history today.